INCREASING STUDENTS’ READING SKILL THROUGH DIRECTED READING THINKING ACTIVITY (DRTA) STRATEGY : CLASSROOM ACTION RESEARCH AT THE THIRD SEMESTER STUDENTS OF ENGLISH DEPARTMENT OF POLITEKNIK NEGERI MADIUN - Moh. Farid Maftuh (INOVISH JOURNAL, 2017)
Abstract: This is aimed at: identifying whether or not DRTA improves students’ reading skill at the third semester of English Department of PNM. The method used in this research was classroom action research which had been conducted in two cycles at the third semester students of English Department of Madiun State Polytechnic. There were two kinds of data; qualitative data and quantitative data. The qualitative data were collected through the questionnaires, observation, field note, the interview of the students’ progress during teaching and learning process, and for quantitative data were collected by using test (pre and post test). The research finding shows that the use of DRTA could improve students’ reading skills and the classroom situation of Reading class. The improvement of students’ reading skill includes: (1) Students are identify the main idea of the text; (2) Students are able to find specific information in the text; (3) Students are able to find the purpose of the text; (4) Students are able to infer meaning ; (5) Students are able to determine references. Besides that the mean score of pre test, first post test, and the second post test that is 56.8, 62.26, and 68.66. The classroom situation also improved. The improvement class situation include: (1) The students are more active and enthusiastic in teaching learning process; (2) The students pay attention and involve in the activities during teaching learning process and (3) The Students feel more excited with the text used in the teaching learning process. Considering the result of this study, the implementation of DRTA in teaching reading conducted at English Department of PNM bring positive effects toward the students’ reading ability, so that it is important for lecturer to be consistent in implementing in order that the result of teaching and learning would be maximal. Finally, it is hoped for the researcher to use the result as aditional reference for further research especially research dealing with DRTA in teaching reading.